EFFECT OF USING CALCIUM CARBONATE (CaCO3) IN SURFACE COATING ON LIQUID ABSORPTION OF PAPER AND SOME PRINTABILITY PARAMETERS - (:unkn) unknown (EDITURA ACAD ROMANE, 2020)
For quality printing results that require detail, the smooth paper surface, absorbency, color and gloss are of great importance. Since the desired surface properties cannot be obtained even in well-polished paper, smooth paper surfaces can be obtained by sizing and coating processes. The aim of this study was to investigate the effect of different amounts of calcium carbonate, added into the surface coating formulation, on liquid absorbency and printability of paper. Paper coating formulations were created by adding 1%, 2.5%, 5% and 7.5% calcium carbonate to an equal amount of cationic starch binder. The obtained coating formulations were applied to the surface of standard pieces of paper with a lab coater. Water absorbency and drop contact angle of all papers (base paper and surface-treated paper) were measured by using the sessile droplet method and then their surface energies were calculated. After the gloss and color changes of the test papers were determined, test prints were applied on their surface with offset printing ink. The effect of surface treatments on the printability characteristics of the paper was examined in detail. It was emphasized that the amount of calcium carbonate used in cationic starch should be optimized with regard to the absorbency and printability of the paper.
Keywords: paper coating; surface chemistry; surface energy; water absorption; printability; calcium carbonate; PHYSICAL-PROPERTIES; INK; QUALITY